ANALISIS PENGARUH SOLVABILITAS, LIKUIDITAS, INVESTASI DAN INFLASI TERHADAP PERTUMBUHAN LABA DI SEKTOR PERBANKAN BURSA EFEK INDONESIA TAHUN 2018-2022 - Ferayani, Made Dwi; Julia Dewi, Luh Putu Sinta (Komunitas Manajemen Kompetitif, 2023)
This study aims to identify and analyse the impact of solvency, liquidity, investment and inflation on profit growth in the IDX banking sector. This type of research is quantitative. It uses secondary data in the form of financial statements and annual reports of banking companies for the period 2018-2022, published by the Indonesia Stock Exchange. In analysing the data, the data analysis technique used is multiple linear regression analysis. Data collection technique used is documentation technique. Data analysis technique is SPSS. The results show that the higher the solvency, the lower the profit growth rate, and vice versa, the lower the solvency, the higher the profit growth rate. The results show that the higher the liquidity, the lower the profit growth, and vice versa the higher the liquidity, the higher the profit growth The higher the investment, the higher the profit growth, and vice versa the lower the investment, the lower the profit growth The higher the inflation, the lower the profit growth, and vice versa the lower the inflation, the higher the profit growth.